2019
DOI: 10.24258/jba.v15i3.516
|View full text |Cite
|
Sign up to set email alerts
|

Pemerintahan Kolaboratif Sebagai Solusi Kasus Deforestasi di Pulau Kalimantan: Kajian Literatur

Abstract: Indonesia is a country with the largest biodiversityin the world. It has a rich forest both in land and the surface of the land, however the forest-related problemalso occurs in Indonesia. One of the largest islands in the world, namely Kalimantan Island has the largest forest distribution in Indonesia. In fact, it cannot be separated from deforestation issue for plantation, mining, and new residential areas reasons. If there is no monitoring, derforestation will produce increasingly severe forests damage, glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…Strengthening participation is performed out through aspects of political efficacy, motivation, and institutions (13,16). Political efficacy can be seen from two dimensions, both internally and externally.…”
Section: Stakeholder Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Strengthening participation is performed out through aspects of political efficacy, motivation, and institutions (13,16). Political efficacy can be seen from two dimensions, both internally and externally.…”
Section: Stakeholder Analysismentioning
confidence: 99%
“…The development paradigm shift has placed humans and society apart from being central but also as subjects of development (2). This means that the presence of human resources will make a major contribution to the sustainability of the program (16). The previous research that has been explored uses the concept of community group participation such as in advocating policy issues (17), rural primary health care system programs (18), malaria control (19,20), disaster preparedness (21), sustainable tourism development (22), youth civic engagement (23), vegetable traceability systems (24).…”
Section: Introductionmentioning
confidence: 99%
“…Then, in a research on Legal Aspects of Community Empowerment around the Tarakan Protected Forest [15], it is found that community empowerment around the forest has a very strategic role in preventing and eradicating forest damage in order to preserve Tarakan Protected Forest. Furthermore, Kamnoonwatana in Tando et al [16], in his research on Collaborative Government as a Solution to Deforestation Cases in Kalimantan Island: Literature Review, states that the role of the private sector in collaborative government is of course necessary, especially because the private sector has a large capital both from technicians, finance, managerial that are already standardized and a good pattern of work.…”
Section: Previous Studymentioning
confidence: 99%
“…Kerjasama dengan pemangku kepentingan tentunya didukung dari internal organisasi, penguatan kelembagaan dirasa sangat penting dalam pemerintahan kolaboratif ini sebagai salah satu modal dalam melaksanakan kerjasama (Tando, Sudarmo, & Haryanti, 2019). Proses pemberdayaan bertujuan dalam rangka peningkatan kemampuan dan kemandirian masyarakat untuk mendapatkan manfaat yang bersumber dari kawasan hutan tersebut.…”
Section: Hasil Dan Pembahasanunclassified